On the Edge of the World: Examining Pro-Environmental Outcomes of Last Chance Tourism in Kaktovik, Alaska - Miller, Lauren (Clemson University Libraries, 2019)
Travel to impact-sensitive destinations has been on the rise in recent years. Coined last chance tourism (LCT), visitors are flocking to these imperiled destinations to see them before they are gone. To off-set their presence, which ultimately contributes to site degradation, a possible positive outcome of these LCT experiences is the creation of environmental ambassadors. Utilizing data collected from 189 visitor surveys, the purpose of this study is to provide a basis for understanding the visitor experience and outcomes of boat-based polar bear viewing in the Kaktovik area of the Arctic National Wildlife Refuge. This study contributes to current literature by examining a diversity of experiential factors in a LCT destination and how they contribute to pro-environmental outcomes (pro-environmental and ambassadorship behavior). A typology of visitors was created based on importance of various trip elements, and demographic and trip characteristics were examined by resulting groups. Analyses show that the polar bear viewing experience does have the potential to increase visitors’ pro-environmental and ambassadorship behavioral intentions. Regression analyses revealed, for the sample population as a whole, that total minutes educated and the occurrence of an epiphany had a positive impact on visitors’ reported pro-environmental behavior and ambassadorship intentions. Surprisingly, seeing more polar bears was negatively related to these same intentions. Implications for management of similar experiences are discussed.